Psychometric properties of an oral health literacy scale for people living with diabetes - Andréa Maria Eleutério de Barros Lima MARTINS; Ana Maria Rodrigues SANTOS; Gizelton Pereira ALENCAR; João Gabriel Silva SOUZA; Maria Alice Aguiar SOARES; Maria Barros Lima MARTINS; Marise Fagundes SILVEIRA; Melissa Barral MAIA; Paula Karoline Soares FARIAS; Raquel Conceição FERREIRA; Rodrigo Alves PINTO; Thaisa Soares CRESPO; et al. (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract This study evaluated the construct validity of the instrument Oral Health Literacy among diabetics. A probabilistic random sample of 239 diabetics from an infinite population answered the 10 items of the questionnaire. The structural validity was assessed by confirmatory factor analysis and goodness of fit, chi-square per degrees of freedom ratio (X2/df), comparative fit index (CFI), goodness-of-fit index (GFI), and root-mean-square error of approximation (RMSEA). Internal consistency was estimated by the average variance extracted (AVE) and composite reliability (CR). The scores were dichotomized with the upper limit of the 95% confidence interval as the cutoff point. The three-dimensional model presented good quality parameters (X2 /df = 2.459; CFI = 0.988; TLI = 0.981) and poor RMSEA (0.078). Internal consistency was adequate; AVE for the Access, Understand/appraise, and Apply subscales were 0.831, 0.981, and 0.954 and the CR for these subscales were 0.893, 0.962, and 0.822, respectively. Inadequate literacy ranged from 41.8 to 48.1%. The three-dimensional model identified (access, understand/appraise, and apply) showed structural validity, good internal consistency, and understandability.